HYBRIDIZATION-BASED NUCLEIC ACID AMPLIFICATION TEST TERHADAP CARTRIDGE-BASED NUCLEIC ACID AMPLIFICATION TEST TERKAIT MULTIDRUG-RESISTANT TUBERCULOSIS (Hybridization-Based Nucleic Acid Amplification Test towards Catridge-Based Nucleic Acid Amplification Test in Multidrug-Resistant Tuberculosis) - Ivana Agnes Sulianto; Ida Parwati; Nina Tristina; Agnes Rengga I (Indonesian Association of Clinical Pathologist and Medical laboratory, 2015)
Indonesia has high burden of multidrug-resistant tuberculosis (MDR-TB). Cartridge-based nucleic acid amplification test (CB-NAAT),which is recommended as a diagnostic method of MDR-TB by World Health Organization, is faster in achieving the result. This methoddetermines MDR-TB only from the rifampisin resistance, by detecting mutations that occur on the 81 bp hot-spot region of the rpoBgene. The isoniazid resistance is not included in the determination of MDR-TB by this method. Hybridization-based NAAT (HB-NAAT)detects MDR-TB not only from the rifampisin resistance (codon 526 and 531 rpoB gene), but also from the isoniazid resistance (codon315 katG gene). The aim of this study was to know the validity of the HB-NAAT in detecting MDR-TB using sputum with CB-NAATas the gold standard in a diagnostic study. All of 51 sputums were collected during June 2013 from patients suspected pulmonaryMDR-TB at Dr. Hasan Sadikin General Hospital. The result of CB-NAAT were 16 MDR-TB, 12 TB non MDR, and 23 non TB. HB-NAATexamination results were 3 MDR-TB, 25 TB non MDR (3 RMR, 6 IMR, 16 susceptible) and 23 non TB. The sensitivity of HB-NAAT was18.75% and specificity 100%. Low sensitivity values may due to the high mutation variations in the samples. So it could not be detectedonly by codons 526 and 531 for rifampisin resistance. For the detection of isoniazid resistance, HB-NAAT have optimal primer at lowconcentrations and it also need more than katG genes to detect isoniazid resistance. Based on this study, it can be conclued, that HBNAAThas low sensitivity but high specificity in the detecting MDR-TB.